On-Orbit Validation of the OpenHarmony Real-Time Operating System Based on the Dalian-1 Lianli Satellite - Wenlong Zhang; Yuchi Chen; Guoliang Xue; Bojuan Lei; Ye Xia; Xiaozhou Yu (Space: Science & Technology)
The Dalian-1 Lianli satellite, a 17-kg 12U high-resolution remote sensing CubeSat, was developed to validate a series of innovative technologies, including submeter high-resolution remote sensing imaging, the high-reliability OpenHarmony real-time operating system (RTOS), and the nontoxic hydroxylamine nitrate propulsion system. Launched on 2023 May 10, aboard the Tianzhou-VI cargo spacecraft, the satellite was successfully deployed into orbit on 2024 January 18, following 253 d of in-orbit storage at the China Space Station. Most traditional micro/nanosatellites have poor reliability and real-time performance due to the lack of an RTOS. The satellite uses the free, high-reliability OpenHarmony RTOS with a small kernel for memory-limited microcontroller subsystems. The OpenHarmony RTOS was ported to 3 attitude determination subsystems—a magnetometer, a digital interface sun sensor, and an attitude measurement unit—to test its feasibility in micro/nanosatellites. The ground test and on-orbit verification focused on real-time performance and reliability. Ground tests indicated that the task switching time of the OpenHarmony RTOS averaged ≤2 μs, and the 3 subsystems continuously and stably operated for more than 1,000 h, and the stable update rate of data for all 3 subsystems had been substantially improved. During on-orbit operations, the telemetry data from the 3 subsystems were normal, demonstrating high stability and reliability and the ability to quickly respond to external events or data. These results lead to the conclusion that the real-time performance and reliability of the subsystems were substantially enhanced after being ported with the OpenHarmony RTOS. Additionally, with the assistance of the 3 subsystems, the Dalian-1 Lianli satellite successfully captured remote sensing images with a resolution better than 1 m, meeting the expected requirements. It is anticipated that in future space missions, more micro/nanosatellites will adopt subsystems ported with the OpenHarmony RTOS.